2002
DOI: 10.1002/bit.10361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complexing agents on reduction of Cr(VI) by Desulfovibrio vulgaris ATCC 29579

Abstract: The reduction of Cr(VI) at the expense of molecular hydrogen was studied using resting cells of Desulfovibrio vulgaris ATCC 29579 in anaerobic resting cell suspensions in MOPS buffer. Bioreduction occurred only in the presence of ligands or chelating agents (CO32-, citrate, NTA, EDTA, DTPA). The stimulatory effect of these ligands on the rate of Cr(VI) reduction was correlated (r = 0.988) with the strength of the ligand/chelate complex of Cr(III). The data are examined with respect to likely solution and redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 41 publications
5
50
0
Order By: Relevance
“…The reaction was initiated by the addition of sodium formate (1 ml, 25 mM final concentration) and a sample was withdrawn immediately for estimation of the initial Cr(VI) concentration. Timed samples were successively withdrawn, centrifuged (12 000 g, 4 min; IEC Centra M bench centrifuge) and supernatants were assayed by the diphenyl carbazide method (Mabbett et al, 2002) to estimate the residual Cr(VI) concentration. Removal of Cr(VI) was expressed as the percentage of Cr(VI) removed from the solution as compared to the initial concentration.…”
Section: Assay Of Pd(ii)mentioning
confidence: 99%
“…The reaction was initiated by the addition of sodium formate (1 ml, 25 mM final concentration) and a sample was withdrawn immediately for estimation of the initial Cr(VI) concentration. Timed samples were successively withdrawn, centrifuged (12 000 g, 4 min; IEC Centra M bench centrifuge) and supernatants were assayed by the diphenyl carbazide method (Mabbett et al, 2002) to estimate the residual Cr(VI) concentration. Removal of Cr(VI) was expressed as the percentage of Cr(VI) removed from the solution as compared to the initial concentration.…”
Section: Assay Of Pd(ii)mentioning
confidence: 99%
“…Glucose, by active uptake, enhances the biosynthesis of chromate reductase as mentioned in Figure 7. Studies by Mabbett et al (2002) show the presence of low molecular organic molecules such as citrate protected the chromate reductase enzymes from inactivation by removing toxic products of microbial reduction and a close connection between the amount of Cr (VI) reduced and equilibrium constants of Cr-ligand complexes with more Cr (VI) being reduced with much stronger complexes. Succinate, on the other hand, did not show any (Bae et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that resting cells of D. vulgaris ATCC 29579 (Lovley and Phillips, 1994;Mabbett et al, 2002) and a new Desulfovibrio sp. (Oz7) isolated from a metal-contaminated site were able reduce Cr(VI) at concentrations of V500 AM, but only in the presence of a ligand species able to complex the Cr(III) product (Mabbett et al, 2002).…”
Section: Reduction Of Cr(vi) Using Resting Cells Of Desulfovibrio Sppmentioning
confidence: 98%
“…(Oz7) isolated from a metal-contaminated site were able reduce Cr(VI) at concentrations of V500 AM, but only in the presence of a ligand species able to complex the Cr(III) product (Mabbett et al, 2002). The addition of complexing agents may be impractical or uneconomical industrially.…”
Section: Reduction Of Cr(vi) Using Resting Cells Of Desulfovibrio Sppmentioning
confidence: 99%
See 1 more Smart Citation